Topological analysis of the lipoprotein organophosphate hydrolase from Sphingopyxis wildii reveals a periplasmic localisation. Issue 19 (31st August 2017) - Parthasarathy, Sunil; Parapatla, Hari; Siddavattam, Dayananda
Abstract: Organophosphate hydrolase (OPH) is a membrane-associated lipoprotein. It translocates across the inner membrane via the twin-arginine transport pathway and remains anchored to the periplasmic face of the inner membrane through a diacylglycerol moiety linked to the invariant cysteine residue found at the junction of a SpaseII cleavage site. Due to the existence of a transmembrane helix at the C-terminus of the mature OPH, an inner-membrane topology was predicted suggesting the C-terminus of OPH is cytoplasmic. The predicted topology was validated by generating OPH variants either fused in-frame with β-lactamase or with unique cysteine residues. Sphingopyxis wildii cells expressing OPH variants with Bla fused at the N-terminal, C-terminal or central regions all grew in the presence of ampicillin. Supporting the β-lactamase reporter assay, the OPH variants having unique cysteine residues at different strategic locations were accessible to the otherwise membrane-impermeant PEG-Mal (methoxypolyethylene glycol maleimide) revealing that, with the exception of the lipoprotein anchor, the entire OPH is in the periplasmic space. Abstract : The inner-membrane topology of organophosphate hydrolase in Sphingopyxis wildii .